TINDAK PIDANA TERORISME: SEJARAH, AKAR PERSOALAN, DAN UPAYA PENANGGULANGANNYA - Duwi Handoko; Hulaimi; Lewiaro Laila; Rahmad Alamsyah (JURNAL SOSIO-KOMUNIKA, 2022)
Human motivation to do something (both positive and negative) driven by internal and environmental factors certainly cannot be answered clearly and completely. One of the human motivations from the negative side is humans who are motivated to carry out acts of terrorism. Therefore, this study formulates the problem of how is the history of terrorism crimes? What are the root causes of the crime of terrorism? and what are the efforts to prevent and eradicate criminal acts of terrorism? The type of this research is normative legal research. The data collection method used is a literature study by conducting a study of the literature related to the object of research. Data analysis was carried out systematically based on the formulation of the problem and described qualitatively. The history of criminal acts of terrorism starting from the traditional to the modern is an act of violence that is void (in vain) to be carried out. The root problems that gave rise to criminal acts of terrorism were initially only related to poverty, injustice, and social inequality. However, at this time, the root causes of the emergence of the terrorism movement are using the issue of religious elements as a weapon to inflame the resistance movement. The interpretation of the teachings of religious elements encourages a few groups to carry out terror movements. Efforts to prevent and eradicate criminal acts of terrorism, among others, can be carried out by conducting early detection and deterrence to eliminate the growth and development of terrorism ideology and activities.